Defective homologous recombination DNA repair as therapeutic target in advanced chordoma - Gröschel, Stefan; Hübschmann, Daniel; Raimondi, Francesco; Horak, Peter; Kleinheinz, Kortine; Chudasama, Priya; Heilig, Christoph E.; Eils, Roland; Kalle, Christof von; Scholl, Claudia; Stenzinger, Albrecht; Brors, Benedikt; et al. (Nature Communications, 2019)
Chordomas are rare bone tumors with few therapeutic options. Here we show, using whole-exome and genome sequencing within a precision oncology program, that advanced chordomas (n = 11) may be characterized by genomic patterns indicative of defective homologous recombination (HR) DNA repair and alterations affecting HR-related genes, including, for example, deletions and pathogenic germline variants of BRCA2, NBN, and CHEK2. A mutational signature associated with HR deficiency was significantly enriched in 72.7% of samples and co-occurred with genomic instability. The poly(ADP-ribose) polymerase (PARP) inhibitor olaparib, which is preferentially toxic to HR-incompetent cells, led to prolonged clinical benefit in a patient with refractory chordoma, and whole-genome analysis at progression revealed a PARP1 p.T910A mutation predicted to disrupt the autoinhibitory PARP1 helical domain. These findings uncover a therapeutic opportunity in chordoma that warrants further exploration, and provide insight into the mechanisms underlying PARP inhibitor resistance., Chordomas are rare bone tumors with limited therapeutic options. Here, the authors identify molecular alterations associated with defective homologous recombination DNA repair in advanced chordomas and report prolonged response in a patient treated with a PARP inhibitor, which later acquired resistance due to a newly gained PARP1 mutation.
Gesehen am 03.06.2019